APPLICATIONS TO MANAGEMENT OF HARD SKILL AND SOFT SKILL LIBRARIES TO REALIZE THE IMPLEMENTATION OF PRIMARY SERVICES IN HIGHER EDUCATIONAL LIBRARY IN THE SOCIETY ERA 0.5 IN ORGANIZATIONAL PSYCHOLOGICAL PERSPECTIVE - BAKHTIYAR (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Libraries in the digitalization era should be equipped with renewable information and communication technology. There has been an explosion and explosion of information, creating a need for information for the "net generation", more varied and always wants to fulfill all information needs up to date accurately, quickly, and transparently. A good, reliable, and qualified librarian is obliged to have the ability to master hard skills, soft skills and spiritual skills, so that they are able to provide excellent humane services to library users. The purpose of this study is to describe the soft skills of librarians in realizing excellent library services. The method in this study uses a historical approach research method. Literature study data collection Data analysis using content analysis, comparative analysis. The results of research on the soft skills of librarians in realizing excellent library services in general have been capable of quite well including; (1). listening skills. (2). communication skills (3). interpersonal skills (4). public relations skills. (5). leadership and teamwork skills.